Formation of β′ phase in LPSO structures in an Mg88Co5Y7 alloy - Q.Q. Jin; X.H. Shao; Y.T. Zhou; B. Zhang; S.J. Zheng; X.L. Ma (Journal of Magnesium and Alloys, 2022)
Formation of β′ phase in long-period stacking ordered (LPSO) structures in an Mg88Co5Y7 (at.%) alloy after aging at 200 °C for 24 h or electron beam (EB) irradiation has been studied by high-angle annular dark-field scanning transmission electron microscopy (HAADF-STEM). β′ phase was precipitated only in the Mg matrix but not in LPSO structures after aging at 200 °C for 24 h. LPSO structure containing stacking defects transforms into the β′-long phase during EB irradiation, which plays a key role in accelerating solute atoms’ diffusion. New complex β′(LPSO) structures formed in the alloy after EB irradiation, such as β′(12H) structure with an orthorhombic lattice (Mg7Y, Cmcm, a = 2a0 = 0.642 nm, b = 43a0 = 2.27 nm, c = 6c0 = 3.12 nm).